Diese Präsentation wurde erfolgreich gemeldet.
Wir verwenden Ihre LinkedIn Profilangaben und Informationen zu Ihren Aktivitäten, um Anzeigen zu personalisieren und Ihnen relevantere Inhalte anzuzeigen. Sie können Ihre Anzeigeneinstellungen jederzeit ändern.

Factor Theorem and Remainder Theorem

3.222 Aufrufe

Veröffentlicht am

Factor Theorem and Remainder Theorem. Mathematics10 Project under Mrs. Marissa De Ocampo. Prepared by Danielle Diva, Ronalie Mejos, Rafael Vallejos and Mark Lenon Dacir of 10- Einstein. CNSTHS.

Veröffentlicht in: Bildung
  • Loggen Sie sich ein, um Kommentare anzuzeigen.

Factor Theorem and Remainder Theorem

  1. 1. F a C Ro t Theorem R e M a i N d e R THEOREM
  2. 2. REMAINDER THEOREM: If the polynomial P(X) is divided by X-C, then the remainder is P(C). FACTOR THEOREM: If the remainder comes out to be 0 (zero), then X-C is a factor of P(X).
  3. 3. E SM a x L p e
  4. 4. f(x)= x4 – 13x2 + 36 𝑝 𝑞 = ±1,±2,±3,±4,±6,±9,±12,±18,±36 ±1 Possible roots: ±1, ±2, ±3, ±4, ±6, ±9, ±12, ±18, ±36 1.
  5. 5. If x= 1: f(1) = (1)4 – 13(1)2 + 36 = 1 – 13(1) + 36 = 1 – 13 + 36 = 24 Therefore, x=1 is not a root and (x-1) is not a factor. If x= -1: f(-1) = (-1)4 – 13(-1)2 + 36 = 1 – 13(1) + 36 = 1 – 13 + 36 = 24 Therefore, x=-1 is not a root and (x+1) is not a factor.
  6. 6. If x= 2: f(2) = (2)4 – 13(2)2 + 36 = 16 – 13(4) + 36 = 16 – 52 + 36 = 0 Therefore, x=2 is a root and (x-2) is a factor. If x= -2: f(-2) = (-2)4 – 13(-2)2 + 36 = 16 – 13(4) + 36 = 16 – 52 + 36 = 0 Therefore, x=-2 is a root and (x+2) is a factor.
  7. 7. If x= 3: f(3) = (3)4 – 13(3)2 + 36 = 81 – 13(9) + 36 = 81 – 117 + 36 = 0 Therefore, x=3 is a root and (x-3) is a factor. If x= -3: f(-3) = (-3)4 – 13(-3)2 + 36 = 81 – 13(9) + 36 = 81 – 117 + 36 = 0 Therefore, x=3 is a root and (x-3) is a factor.
  8. 8. Since the exponent of the polynomial function is 4, there should be four roots and four factors. The roots of the polynomial function, f(x) = x4 – 13x2 + 36, are ± 2 𝑎𝑛𝑑 ± 3 . The factors of the polynomial function are (x-2) (x+2) (x-3) (x+3).
  9. 9. f(x) = x2– 12x + 9 𝑝 𝑞 = ±1,±3,±9, ±1 if x = 1 = 12- 10(1) + 9 = 1 -10 + 9 =0 Therefore, x=1 is a root and (x-1) is a factor. 2.
  10. 10. If x = -1 = 12- 10(-1) + 9 = 1 +10 + 9 =20 Therefore, x=-1 is a not a root and (x+1) is not a factor. if x = 3 = 32- 10(3) + 9 = 9 - 30 + 9 = -2 Therefore, x=3 is a not root and (x-3) is not a factor.
  11. 11. if x = -3 = -32- 10(-3) + 9 = 9 + 30 + 9 = 48 Therefore, x=-3 is not a root and (x+3) is a not factor. if x = 9 = 92- 10(9) + 9 = 81 -90 + 9 = 0 Therefore, x=9 is a root and (x-9) is a factor.
  12. 12. If x =- 9 = 92- 10(9) + 9 = -81 + 90 + 9 = 18 Therefore, x=-9 is not a root and (x+9) is not a factor. Since the exponent of the polynomial function is 2, there should be two roots and two factors. The roots of the polynomial function, f(x) = x2– 12x + 9 ate +1 𝑎𝑛𝑑 + 9. The factors of the polynomial function are (x-1) (x-9)
  13. 13. Danielle Erika L. Diva Ronalie C. Mejos Mark Lenon F. Dacir Rafael C. Vallejos MEMBERS X- Einstein

×